High-temperature-resistant nano inorganic binder as well as preparation method and application thereof

By using nanoscale fly ash, calcium oxide and fly ash flotations, and using strong alkali treatment to activate SiO2 and Al2O3, a high polymerization CaO-SiO2-Al2O3 system is formed, and the inorganic binder is solved on metal materials. The poor adhesion and high cost problems achieve efficient and low-cost adhesion effect.

CN119461904APending Publication Date: 2025-02-18CHINA ENERGY INVESTMENT CORP LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311000065.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-09
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Existing inorganic adhesives have poor adhesion in bonding metal materials, and in order to improve high temperature resistance and adhesion, a variety of complex ingredients are needed, resulting in high product costs and complex preparation processes.

Method used

Nano-scale fly ash, calcium oxide and fly ash flotations are used as the main raw materials, and SiO2 and Al2O3 are released through strong alkali (such as NaOH) treatment to form a CaO-SiO2-Al2O3 system with high polymerization and improve bonding performance.

Benefits of technology

Excellent bonding performance to inorganic materials and metal materials has been achieved, the shear strength and tensile strength have been significantly improved, the maximum service temperature can reach 1800℃, and the process is simple and the cost is low.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004386189970000111
    Figure BDA0004386189970000111
  • Figure HDA0004386189980000011
    Figure HDA0004386189980000011
  • Figure HDA0004386189980000012
    Figure HDA0004386189980000012
Patent Text Reader

Abstract

The invention provides a high-temperature-resistant nano inorganic binder, which is prepared from the following raw materials in percentage by mass: 20 to 50 percent of fly ash, 5 to 30 percent of calcium oxide, 5 to 25 percent of alkali liquor, 10 to 30 percent of fly ash flotation substance and 10 to 30 percent of water, and the granularity of the fly ash, the calcium oxide and the fly ash flotation substance is less than 500nm. The invention further provides a preparation method, application and a curing method of the high-temperature-resistant nano inorganic binder. The nano inorganic binder provided by the invention has excellent bonding performance and high temperature resistance, can be suitable for bonding of various materials, especially inorganic materials and metal materials, is simple in composition, low in raw material cost and wide in raw material source, can effectively utilize industrial wastes such as fly ash, fly ash flotation substances and the like, and is suitable for industrial production. And moreover, the preparation process is simple and convenient, has good industrial practicability and is suitable for large-scale production and application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of adhesives, and in particular to a high temperature resistant nano inorganic adhesive, a preparation method and use thereof, and further to a curing method of the high temperature resistant nano inorganic adhesive. Background Art

[0002] In the fields of construction, metallurgy, steel, etc., inorganic bonding is widely used and has developed very rapidly. As a bonding method, its application solves a large number of key production technology problems in bonding and has a very broad development prospect.

[0003] Inorganic binders can be divided into melt-curing type, volatilization-curing type, water-curing type, reaction-curing type, etc. according to the different curing methods. Among them, reaction-curing inorganic binders are the most widely used and have the most application value. Reaction-curing inorganic binders generally include two categories: phosphates and silicates. Since phosphate binders are too brittle and not resistant to high temperatures, silicate binders are widely used in actual production.

[0004] However, inorganic binders also have their application limitations, mainly including the following two aspects: 1) Inorganic binders have relatively poor adhesion to metal materials; 2) In order to increase the high temperature resistance and adhesion of inorganic binders, more than ten ingredients are usually required to complement each other, resulting in high product costs and extremely complex preparation processes.

[0005] To this end, researchers have conducted a lot of research on inorganic binders and have achieved some results. For example, Chinese patent CN 202010986889.0 provides a high-temperature resistant inorganic binder, which is prepared from raw materials including the following components: 30 to 50 parts by weight of inorganic sol; 15 to 30 parts by weight of primary fiber; 0 to 5 parts by weight of secondary fiber; 3 to 10 parts by weight of alumina clinker; 3 to 8 parts by weight of inorganic powder; 1 to 5 parts by weight of sodium bentonite; 0.1 to 1 part by weight of thickener; the primary fiber is selected from one or more of aluminum silicate fiber, magnesium silicate fiber, zirconium-containing fiber and rock wool fiber; the secondary fiber is selected from one or more of high silica fiber, alkali-free glass fiber, medium alkali glass fiber and organic fiber. The high temperature resistant inorganic binder adopts inorganic sol as the base material and adds other specific content components to achieve good interaction as a whole. The obtained high temperature resistant inorganic binder has a short curing time and can be cured under room temperature conditions. It can be used in the temperature range of 1000°C to 1300°C, and has high bonding strength and good thermal stability.

[0006] For another example, Chinese patent CN 201910346503.7 discloses a water-based high-temperature-resistant inorganic binder and a preparation method thereof. The raw materials are weighed according to the formula: water glass, silica sol, titanium dioxide, magnesium oxide, aluminum oxide, zirconium oxide, glass powder, boron carbide, and water. The above materials are placed in a ball mill and mixed by ball milling for 2-6 hours to obtain a water-based high-temperature-resistant inorganic binder. The binder can be used under rapid cooling conditions from room temperature to 900°C, and has good high-temperature resistance, wear resistance, weather resistance, high self-cleaning and mildew resistance. The water-based high-temperature-resistant inorganic binder has a wide range of applications and is widely used in the fields of construction, military industry, vehicles, ships, bridges, and the protection of inner and outer walls of pipelines. The binder has a strong bonding ability to steel, non-ferrous metals, organic materials, inorganic materials, and various types of thermal insulation materials, has good adhesion to the substrate, and has high bonding strength.

[0007] It can be seen that in order to enhance the adhesion, the existing inorganic binders usually use very complex ingredients, which are costly and have a cumbersome preparation process. Moreover, the adhesion of these inorganic binders to metal materials is still not ideal. Therefore, there is an urgent need to develop an inorganic binder with simple composition, low cost and excellent adhesion performance. Summary of the invention

[0008] In order to make up for the deficiencies in the prior art, an object of the present invention is to provide a high-temperature resistant nano inorganic binder, which has a simple composition, low raw material cost, is easy to prepare, and has excellent bonding properties and high-temperature resistance, especially for inorganic materials and metal materials.

[0009] Another object of the present invention is to provide a preparation method and use of the high temperature resistant nano inorganic binder.

[0010] Another object of the present invention is to provide a curing method for the high temperature resistant nano inorganic binder.

[0011] The first aspect of the present invention provides a high temperature resistant nano inorganic binder, which comprises the following raw materials, by mass percentage: 20-50% fly ash, 5-30% calcium oxide, 5-25% alkali solution, 10-30% fly ash flotation product and 10-30% water, wherein the particle size of the fly ash, calcium oxide and fly ash flotation product is less than 500nm.

[0012] The bonding principle of the high temperature resistant nano inorganic binder provided by the present invention is as follows:

[0013] Fly ash is usually formed at a high temperature of 800 to 1000°C, so a glass body is formed on its surface, and a glass protective layer rich in SiO2 and SiO2-Al2O3 is formed on the surface of the glass body. The obstruction of the protective layer makes it difficult for the soluble SiO2 and Al2O3, which are originally not much inside the fly ash particles, to dissolve out, and their activity is difficult to exert. The inorganic binder provided by the present invention can destroy the protective layer composed of the -Si-O-Si- and -Si-O-Al- networks on the surface of the fly ash through the strong alkali (such as NaOH) in the alkali solution, thereby enabling the activity of the internal soluble SiO2 and Al2O3 to be fully released.

[0014] The internal soluble SiO2 and Al2O3 depolymerize under the action of strong alkali, making [SiO4] 4- and [AlO4] 5- The tetrahedral three-dimensional continuous high-polymerization network depolymerizes into tetrahedral short chains, which further depolymerize into [SiO4] 4- and [AlO4] 5- Such active substances are monomers or dimers with low polymerization degree. These active substances are more likely to polymerize with CaO to form a CaO-SiO2-Al2O3 system. The higher the polymerization degree of the CaO-SiO2-Al2O3 system, the greater the intermolecular force of the polymer, that is, the stronger the ability to resist external forces and not be damaged, and the better the adhesion. Figure 1 As shown, a network of CaO-SiO2-Al2O3 gel systems can be observed in the SEM image. These gels adhere to the surface of the material to form a strong bonding force.

[0015] The nano-scale binder provided by the present invention can also increase the permeability of the binder to inorganic materials, forming a permeable interface area, and has stronger tensile, compressive and shearing resistance than traditional binders. Figure 2 As shown in Figures A and B of , the conventional adhesive forms a distinct interface with the material surface, the intermolecular forces are limited, and the adhesion is difficult to improve. The nano-scale adhesive provided by the present invention can penetrate into the material through the gaps of the inorganic material to form an interaction, thereby reducing the molecular distance, increasing the van der Waals force, and thus improving the adhesion.

[0016] For metal materials, since the surface roughness of metal materials is smaller than that of inorganic materials, traditional adhesives will form a more obvious material interface with the surface of metal materials, and the intermolecular force is also more obviously restricted, resulting in poor viscosity. Figure 3 As shown in Figure A.

[0017] When combined with metal materials, the metasilicic acid and metaaluminic acid generated by the reaction and hydrolysis of SiO2 and Al2O3 with strong alkali will react with the metal surface oxide to generate MSiO3 and M(AlO2)2, thereby increasing the surface roughness of the metal. The nanoscale raw materials used in the present invention can quickly dissolve SiO2 and Al2O3, making it easier for the binder to penetrate into the metal material and get closer to the metal atoms, thereby making the intermolecular force stronger and the bonding force of the binder stronger. Figure 3 As shown in Figure B.

[0018] The nano-scale inorganic binder provided by the present invention is tested for performance, and the shear strength can reach 6-20 MPa, the tensile strength can reach 9-30 MPa, and the use temperature can reach 1500-1800° C. It can be seen that the nano-scale inorganic binder provided by the present invention has excellent bonding performance and high temperature resistance.

[0019] In some preferred embodiments, the high temperature resistant nano inorganic binder may include the following raw materials, by mass percentage: 20-40% fly ash, 5-20% calcium oxide, 10-20% alkali solution, 10-30% fly ash flotation product and 15-25% water.

[0020] In some preferred embodiments, the total amount of fly ash and fly ash flotation products in the high temperature resistant nano inorganic binder is not less than 40% by mass.

[0021] In some preferred embodiments, the median particle size of the fly ash, calcium oxide and fly ash flotation product may be 250-350 nm independently. In some more preferred embodiments, the median particle size of the fly ash and fly ash flotation product may be 300-350 nm independently, and the median particle size of the calcium oxide may be 250-300 nm.

[0022] In some preferred embodiments, the source of fly ash can be fly ash produced by common power plants, which can be crushed or ground to a desired particle size before use.

[0023] In some preferred embodiments, the source of fly ash flotation products can be flotation products produced by common power plant fly ash flotation, which can be crushed or ground to the required particle size before use. In some more preferred embodiments, the fly ash flotation products can contain 35-65% SiO2, 5-35% Al2O3, 5-20% CaO and 1-10% Fe2O3 by mass percentage. In some further preferred embodiments, the fly ash flotation products can contain 60-65% SiO2, 20-25% Al2O3, 10-15% CaO and 3-8% Fe2O3.

[0024] In some preferred embodiments, calcium oxide can be from any common source, such as commercially available products, and can be crushed or ground to a desired particle size before use.

[0025] In some preferred embodiments, the alkali solution can be a NaOH solution or KOH solution with a mass percentage concentration of 10 to 25%, for example, about 10%, about 12%, about 15%, about 18%, about 20%, about 22%, about 25% or any combination of concentration intervals. The alkali solution can be prepared from a high concentration alkali solution or a solid base. In some more preferred embodiments, the alkali solution can be a NaOH solution with a mass percentage concentration of 12 to 18%. In some most preferred embodiments, the alkali solution can be a NaOH solution with a mass percentage concentration of 15%.

[0026] The second aspect of the present invention provides a method for preparing the high temperature resistant nano inorganic binder, which comprises adding the alkali solution and water to the fly ash, fly ash flotation product and calcium oxide, mixing, heating to 80-120°C, and maintaining for 4-10 hours to obtain the binder.

[0027] In some preferred embodiments, the preparation method may further include: firstly mixing the nano-scale fly ash, fly ash flotation product and calcium oxide, then adding the alkali solution and water thereto, mixing well, heating to 80-100° C., and maintaining for 4-8 hours to obtain the product.

[0028] The third aspect of the present invention provides the use of the high temperature resistant nano inorganic binder described in any one of the above technical solutions or the high temperature resistant nano inorganic binder prepared by the preparation method described in any one of the above technical solutions as a binder for inorganic materials or metal materials.

[0029] In some preferred embodiments, the inorganic material includes but is not limited to ceramics, bricks (such as refractory bricks), and the like.

[0030] In some preferred embodiments, the metal material includes but is not limited to stainless steel, cast iron, copper, aluminum, and the like.

[0031] The fourth aspect of the present invention provides a method for curing the high-temperature resistant nano inorganic binder described in any one of the above technical solutions or the high-temperature resistant nano inorganic binder prepared by the preparation method described in any one of the above technical solutions, and the curing method is: the high-temperature resistant nano inorganic binder is cured at 60 to 200°C for 12 to 24 hours after coating.

[0032] In another embodiment, the curing method is: the high temperature resistant nano inorganic binder is cured at 60-200° C. for 4-8 hours after coating, and then high temperature reinforcement is performed at 600-1500° C. for 2-14 hours. This curing method is applicable to high temperature use environments.

[0033] The technical solution provided by the present invention has the following advantages:

[0034] (1) The nano inorganic adhesive provided by the present invention has excellent bonding properties and can form an obvious penetration zone between the adhesive and the bonding material, so the bonding force is stronger and the bonding effect is better, and it can be applied to the bonding of various materials, especially inorganic materials and metal materials.

[0035] (2) The nano inorganic binder provided by the present invention also has good high temperature resistance, and the maximum operating temperature can reach 1800°C.

[0036] (3) The nano inorganic binder provided by the present invention has a simple composition, low raw material cost and a wide range of sources, and can effectively utilize industrial waste fly ash, fly ash flotation products, etc., to achieve the recycling of solid waste, which is environmentally friendly.

[0037] (4) The nano inorganic binder provided by the present invention has a simple preparation process, strong operability and high safety, and thus has good industrial applicability and is suitable for large-scale production and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 This is a SEM image of the nano inorganic binder of the present invention after curing (magnified 10,000 times);

[0039] Figure 2 It is a schematic diagram of the principle of inorganic binders bonding inorganic materials, wherein Figure A represents a traditional inorganic binder and Figure B represents the nano inorganic binder of the present invention;

[0040] Figure 3 It is a schematic diagram of the principle of bonding metal materials with inorganic adhesives, wherein Figure A represents a traditional inorganic adhesive and Figure B represents the nano inorganic adhesive of the present invention. DETAILED DESCRIPTION

[0041] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments.

[0042] Unless otherwise specified, the raw materials or reagents used in the examples and comparative examples of the present invention are commercially available products.

[0043] The fly ash used in the embodiments and comparative examples of the present invention comes from a power plant and is put into a mill before use and ground to a particle size of less than 500 nm, with a median particle size of 325 nm.

[0044] The fly ash flotation product used in the embodiments and comparative examples of the present invention comprises 61% SiO2, 23% Al2O3, 11% CaO and 5% Fe2O3 by mass percentage. It is ground to a particle size of less than 500 nm before use, with a median particle size of 325 nm.

[0045] The calcium oxide used in the examples and comparative examples of the present invention was ground to a particle size of less than 500 nm before use, and the median particle size was 257 nm.

[0046] The percentages used in the embodiments and comparative examples of the present invention are all mass percentages unless otherwise specified.

[0047] Example 1 Preparation of Inorganic Binder

[0048] The raw material composition is as follows by mass percentage:

[0049] Fly ash: 30%;

[0050] Calcium oxide: 20%;

[0051] 15wt% NaOH solution: 5%;

[0052] Fly ash flotation: 20%;

[0053] Water: 25%.

[0054] Nano-scale fly ash, fly ash flotation product and calcium oxide are weighed in proportion, and then 15% NaOH solution and water are added in proportion, stirred evenly, heated to 90° C., and maintained for 6 hours to obtain a nano-inorganic binder.

[0055] Example 2 Preparation of Inorganic Binder

[0056] The raw material composition is as follows by mass percentage:

[0057] Fly ash: 30%;

[0058] Calcium oxide: 20%;

[0059] 15wt% NaOH solution: 15%;

[0060] Fly ash flotation: 10%;

[0061] Water: 25%.

[0062] Nano-scale fly ash, fly ash flotation product and calcium oxide are weighed in proportion, and then 15% NaOH solution and water are added in proportion, stirred evenly, heated to 90° C., and maintained for 6 hours to obtain a nano-inorganic binder.

[0063] Example 3 Preparation of Inorganic Binder

[0064] The raw material composition is as follows by mass percentage:

[0065] Fly ash: 40%;

[0066] Calcium oxide: 10%;

[0067] 15wt% NaOH solution: 20%;

[0068] Fly ash flotation: 10%;

[0069] Water: 20%.

[0070] Nano-scale fly ash, fly ash flotation product and calcium oxide are weighed in proportion, and then 15% NaOH solution and water are added in proportion, stirred evenly, heated to 90° C., and maintained for 6 hours to obtain a nano-inorganic binder.

[0071] Example 4 Preparation of Inorganic Binder

[0072] The raw material composition is as follows by mass percentage:

[0073] Fly ash: 30%;

[0074] Calcium oxide: 15%;

[0075] 15wt% NaOH solution: 15%;

[0076] Fly ash flotation: 15%;

[0077] Water: 25%.

[0078] Nano-scale fly ash, fly ash flotation product and calcium oxide are weighed in proportion, and then 15% NaOH solution and water are added in proportion, stirred evenly, heated to 90° C., and maintained for 6 hours to obtain a nano-inorganic binder.

[0079] Example 5 Preparation of Inorganic Binder

[0080] The raw material composition is as follows by mass percentage:

[0081] Fly ash: 30%;

[0082] Calcium oxide: 5%;

[0083] 15wt% NaOH solution: 20%;

[0084] Fly ash flotation: 25%;

[0085] Water: 20%.

[0086] Nano-scale fly ash, fly ash flotation product and calcium oxide are weighed in proportion, and then 15% NaOH solution and water are added in proportion, stirred evenly, heated to 90° C., and maintained for 6 hours to obtain a nano-inorganic binder.

[0087] Example 6 Preparation of Inorganic Binder

[0088] The raw material composition is as follows by mass percentage:

[0089] Fly ash: 40%;

[0090] Calcium oxide: 10%;

[0091] 15wt% NaOH solution: 20%;

[0092] Fly ash flotation: 15%;

[0093] Water: 15%.

[0094] Nano-scale fly ash, fly ash flotation product and calcium oxide are weighed in proportion, and then 15% NaOH solution and water are added in proportion, stirred evenly, heated to 90° C., and maintained for 6 hours to obtain a nano-inorganic binder.

[0095] Example 7 Preparation of Inorganic Binder

[0096] The raw material composition is as follows by mass percentage:

[0097] Fly ash: 20%;

[0098] Calcium oxide: 15%;

[0099] 15wt% NaOH solution: 15%;

[0100] Fly ash flotation: 30%;

[0101] Water: 20%.

[0102] Nano-scale fly ash, fly ash flotation product and calcium oxide are weighed in proportion, and then 15% NaOH solution and water are added in proportion, stirred evenly, heated to 90° C., and maintained for 6 hours to obtain a nano-inorganic binder.

[0103] Comparative Example 1 Preparation of Inorganic Binder

[0104] The raw material composition is as follows by mass percentage:

[0105] Fly ash: 40%;

[0106] Calcium oxide: 25%;

[0107] 15wt% NaOH solution: 20%;

[0108] Fly ash flotation: 0%;

[0109] Water: 15%.

[0110] Nano-scale fly ash and calcium oxide are weighed in proportion, and then 15% NaOH solution and water are added in proportion, stirred evenly, heated to 90° C., and maintained for 6 hours to obtain a nano-inorganic binder.

[0111] Comparative Example 2 Preparation of Inorganic Binder

[0112] The raw material composition is as follows by mass percentage:

[0113] Fly ash: 0%;

[0114] Calcium oxide: 25%;

[0115] 15wt% NaOH solution: 20%;

[0116] Fly ash flotation: 40%;

[0117] Water: 15%.

[0118] Nano-scale fly ash flotation product and calcium oxide are weighed in proportion, and then 15% NaOH solution and water are added in proportion, stirred evenly, heated to 90° C., and maintained for 6 hours to obtain an inorganic binder.

[0119] Comparative Example 3 Preparation of Inorganic Binder

[0120] The raw material composition is as follows by mass percentage:

[0121] Fly ash: 25%;

[0122] Calcium oxide: 10%;

[0123] 15wt% NaOH solution: 0%;

[0124] Fly ash flotation: 25%;

[0125] Water: 40%.

[0126] Nano-scale fly ash, fly ash flotation product and calcium oxide are weighed in proportion, and then water is added in proportion, stirred evenly, heated to 90° C., and maintained for 6 hours to obtain a nano-inorganic binder.

[0127] Test Case

[0128] The inorganic binders prepared in Examples 1-7 and Comparative Examples 1-3 were coated on the surface of refractory bricks, fully cured at 100° C. for 6 h, and then high-temperature reinforced at 800° C. for 12 h.

[0129] The tensile strength was tested according to GB / T 2567-2008 “Test method for properties of resin castings”, and the shear force was tested according to GB / T14903-94 “Test method for torsional shear strength of inorganic adhesive sleeves”. The test results are shown in Table 1.

[0130] Table 1 Raw material composition and performance test results of inorganic binder

[0131]

[0132] It can be seen from the results in Table 1 that the inorganic binder prepared by the present invention has excellent bonding strength, and both tensile strength and shear strength are high. However, the inorganic binder prepared in the comparative example lacks the necessary components (i.e., fly ash, fly ash flotation product, and sodium hydroxide), so its bonding performance is far inferior to that of the inorganic binder of the present invention.

[0133] In addition, when the amount of sodium hydroxide is small, its activation effect on fly ash and fly ash flotation products will be reduced, thereby reducing the bonding performance (as shown in Example 1), and when the amount of fly ash and fly ash flotation products is small, a large amount of gel polymer cannot be formed. Therefore, in order to ensure good bonding performance and give play to the synergistic effect of alkali solution, fly ash and fly ash flotation products, it is preferred that the binder contains at least 10% alkali solution and at least 10% fly ash flotation products by mass percentage, and the total amount of fly ash flotation products and fly ash is not less than 40%.

[0134] Unless otherwise defined, the terms used in the present invention have the meanings commonly understood by those skilled in the art.

[0135] The embodiments described in the present invention are for illustrative purposes only and are not intended to limit the scope of protection of the present invention. Those skilled in the art may make various other substitutions, changes and improvements within the scope of the present invention. Therefore, the present invention is not limited to the above embodiments, but is only limited by the claims.

Claims

1. A high temperature resistant nano inorganic binder, characterized in that: The invention comprises the following raw materials by mass percentage: 20-50% fly ash, 5-30% calcium oxide, 5-25% alkali solution, 10-30% fly ash flotation product and 10-30% water, wherein the particle size of the fly ash, calcium oxide and fly ash flotation product is less than 500nm.

2. The high temperature resistant nano inorganic binder according to claim 1, characterized in that: The raw materials include the following by mass percentage: 20-40% of fly ash, 5-20% of calcium oxide, 10-20% of alkali solution, 10-30% of fly ash flotation product and 15-25% of water.

3. The high temperature resistant nano inorganic binder according to claim 1 or 2, characterized in that: The median particle sizes of the fly ash, calcium oxide and fly ash flotation product are independently 250-350 nm.

4. The high temperature resistant nano inorganic binder according to any one of claims 1 to 3, characterized in that: The alkali solution is a NaOH solution or a KOH solution with a mass percentage concentration of 10-25%, preferably a NaOH solution with a mass percentage concentration of 12-18%.

5. The high temperature resistant nano inorganic binder according to any one of claims 1 to 4, characterized in that: Calculated by mass percentage, the fly ash flotation product contains 35-65% SiO2, 5-35% Al2O3, 5-20% CaO and 1-10% Fe2O3.

6. The method for preparing the high temperature resistant nano inorganic binder according to any one of claims 1 to 5, characterized in that: The alkali solution and water are added to the fly ash, fly ash flotation product and calcium oxide, mixed evenly, heated to 80-120° C., and maintained for 4-10 hours to obtain the product.

7. Use of the high temperature resistant nano inorganic binder according to any one of claims 1 to 5 or the high temperature resistant nano inorganic binder prepared by the preparation method according to claim 6 as a binder for inorganic materials or metal materials.

8. The use according to claim 7, characterized in that The inorganic material is one or more of ceramics and bricks; and / or The metal material is one or more of stainless steel, cast iron, copper and aluminum.

9. A method for curing the high temperature resistant nano inorganic binder according to any one of claims 1 to 5 or the high temperature resistant nano inorganic binder prepared by the preparation method according to claim 6, characterized in that: The high temperature resistant nano inorganic binder is cured at 60 to 200° C. for 12 to 24 hours after coating.

10. A method for curing the high temperature resistant nano inorganic binder according to any one of claims 1 to 5 or the high temperature resistant nano inorganic binder prepared by the preparation method according to claim 6, characterized in that: After coating, the high temperature resistant nano inorganic binder is cured at 60-200° C. for 4-8 hours, and then high temperature reinforced at 600-1500° C. for 2-14 hours.

Citation Information

Patent Citations

  • Method for preparing silicon fertilizer through coal gangue

    CN109928782A

  • High-temperature-resistant inorganic binder and preparation method thereof

    CN112063308A